季節海氷域化する北極海における海氷－海洋アルベドフィードバック効果の実証 - 柏瀬, 陽彦; 大島, 慶一郎; 二橋, 創平; Hajo, Eicken; Haruhiko, Kashiwase; Kay, I. Ohshima; Sohey, Nihashi (2017)
第8回極域科学シンポジウム/横断セッション：[IA] 北極国際連携拠点の新展開 12月8日（金）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Interdisciplinary sessions: [IA] New insights of overseas research stations in the Arctic Fri. 8 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object